'From past to future' – deciphering the molecular basis of Alzheimer's disease through the pages of the Journal of Neurochemistry. (21st March 2016) - Cappai, Roberto
Abstract: The Journal of Neurochemistry has made significant contributions to unraveling the molecular basis for Alzheimer's disease during its 60‐year history. To mark its 60th anniversary, this review describes the association between the journal and Alzheimer's disease research – from the early years when Alzheimer's disease was a minor topic in the journal through to the molecular era in the mid‐1980s. This coincided with a number of the highly cited Alzheimer's disease studies which described fundamental aspects of the neurochemistry of Alzheimer's disease and encompassed the themes of oxidative stress and post‐translational modifications, cholinergic system, tau, purification of Aβ, defining the Aβ toxic species, mechanism of amyloid precursor protein processing, and the development of diagnostics and therapeutics. The Journal of Neurochemistry has made significant contributions toward unraveling the molecular, cellular and pathological basis of Alzheimer's disease through its 60 years. This article is part of the 60th Anniversary special issue . Abstract : The Journal of Neurochemistry has made significant contributions toward unraveling the molecular, cellular and pathological basis of Alzheimer's disease through its 60 years. This article is part of the 60th Anniversary special issue .